PEMBERIAN PAKAN TERBATAS SECARA PERIODIK PADA AYAM PEDAGING (LENGHORN) - Darmawati ' (Biogenesis, 2005)
The research was to examine effect restricted feeding in lenghorn chicken, in Labuh Baru Pekanbaru from June -August 2001.  The experiment was conducted  using completely Randomized Design ( R A L )  with three replications. The treatment consist of A (Full  feeding without the fast), B (Three days full feeding, one day the fast), C (six days full feeding, one day the fast). The treatment each consist of five  lenghorn chickens Various parameter such as food consume, increase body weight and food conversion. Data were analyzed using Anava with  DMRT  5 %  level of signification. The result o f this experiment showed that effect  restricted  feeding significance to  food  consume,  increase  body  weight  and  food  conversion  in lenghorn chicken.  The treatment C, was good to increase body weight and food conversion, where as the treatment B to food consume.   Key words : Consume, Conversion, lenghorn chicken, restricted feeding